Code Mixing in Legislative Candidate Campaigns in Denpasar City: A Case Study of Balinese Language Use in the Political Realm - Putu Gede Suarya Natha (Badan Penerbit STIEPARI Press, 2024)
The interest in the Balinese language as a regional language is currently declining, particularly in urban areas. However, it remains frequently used in political campaigns in Bali, especially in Denpasar. This usage typically involves code-switching with other languages. This study aims to uncover the motives behind using the Balinese language in political campaigns and examine the forms of code-switching employed by politicians. The research is descriptive-qualitative, based on verbal data gathered through observing legislative candidates' campaign activities in Denpasar. Data were collected by listening to politicians' speeches. The analysis was conducted using Hymes' communication ethnography theory and Philipsen's speech code theory. Findings indicate that the Balinese language is perceived as a marker of politeness and is considered effective in fostering a sense of closeness between the politicians and the community. The language is used in a code-mixing manner with Indonesian, creating a communication pattern known as a speech code. This includes expressions of prayers or greetings like Om Swastiastu; pronouns such as titiang, Ratu, Ida, Dane; and abstract nouns like ampura, sugra, nunas, and suksma. The Balinese language is predominantly used in the opening and closing parts of speeches, while its use in the content section is limited to the lexical level. The analysis suggests that this code-switching serves as a form of politeness by the communicators.